Managing cultural differences - Harris, Philip R. (Philip Robert) 1926- (Gulf Pub. Co., 1991)
It clearly shows how to develop the cross-cultural expertise essential to succeed in a world of rapid and profound economic, political, and cultural changes. While retaining the wisdom of the previous editions, this new edition provides leading-edge insights into work culture and globalization.